2012
DOI: 10.1007/s00253-012-4275-x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Cgl1427 gene encoding cytidylate kinase in microaerobic growth of Corynebacterium glutamicum

Abstract: The Cgl1427 gene was previously found to be relevant to the microaerobic growth of Corynebacterium glutamicum (Ikeda et al. 2009). In the present work, Cgl1427 was identified as a cytidylate kinase gene (cmk) by homology analysis of its deduced amino acid sequence with that of other bacterial cytidylate kinases (CMP kinases), and on the basis of findings that deletion of Cgl1427 results in loss of CMP kinase activity. Deletion of the cmk gene significantly impaired the growth of C. glutamicum in oxygen-limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore, it is unknown if dCTP/CTP is produced from cytosine and/or uracil residues in hemoplasmas. Recently, cytidylate kinase has been described to have a positive impact on the efficiency of nucleotide synthesis in Corynebacterium glutamicum under microaerobic conditions [49]. Whether or not the presence of this enzyme favors the survival of M. haemofelis and M. haemocanis in oxygen-limited environments needs to be further explored.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is unknown if dCTP/CTP is produced from cytosine and/or uracil residues in hemoplasmas. Recently, cytidylate kinase has been described to have a positive impact on the efficiency of nucleotide synthesis in Corynebacterium glutamicum under microaerobic conditions [49]. Whether or not the presence of this enzyme favors the survival of M. haemofelis and M. haemocanis in oxygen-limited environments needs to be further explored.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this notion, the cmk and deoD genes encode cytidine monophosphate kinase and purine nucleoside phosphorylase, respectively, 20 which are involved in nucleotide biosynthesis, one of the most important metabolic pathways. Previous studies suggested that both genes are required for the growth of several bacterial species, such as Corynebacterium glutamicum , Bacillus subtilis , and E. coli ,22, 23 and thus considered as potential therapeutic drug targets 24 …”
Section: Discussionmentioning
confidence: 99%
“…Of the genes uniquely downregulated at 6.5 h, included Cgl1427/ cmk, cytidyl kinase, Cgl2605/ bioD, thioredoxin reductase. Cgl1427 has been reported to be crucial for maintaining triphosphate pools (ATP, CTP) under oxygen-limiting environments ( Takeno et al, 2013 ) but it’s downregulation implies these early time points are not oxygen-limited. Several genes involved in transport were also significantly downregulated with a cutoff threshold log 2 ratio less than −4.…”
Section: Resultsmentioning
confidence: 99%